Digital mammography in a screening programme and its implications for pathology: a comparative study. Issue 3 (22nd December 2010) - Feeley, Linda; Kiernan, Donal; Mooney, Therese; Flanagan, Fidelma; Hargaden, Gormlaith; Kell, Malcolm; Stokes, Maurice; Kennedy, Margaret
Abstract : Aims: Most studies comparing full-field digital mammography (FFDM) with conventional screen-film mammography (SFM) have been radiology-based. The pathological implications of FFDM have received little attention in the literature, especially in the context of screening programmes. The primary objective of this retrospective study is to compare FFDM with SFM in a population-based screening programme with regard to a number of pathological parameters. Methods: During the study period, 107 818 women underwent screening mammograms with almost equal numbers obtained with each technique (49.9% with SFM vs 50.1% with FFDM). We compared SFM with FFDM using the following parameters: recall rate, diagnostic core biopsy rate, cancer detection rates, B3 rate, B4 rate, preoperative diagnostic rate for malignancy, positive predictive values and tumour characteristics. Results: The recall rate was significantly higher with FFDM (4.21% vs 3.52%, p<0.0001). The overall cancer detection rate of 7.2 per 1000 women screened with FFDM was also significantly higher than the rate of 6.2 per 1000 women screened with SFM (p=0.04). The B3 rate in the SFM group was 1.3 per 1000 women screened versus 2.5 per 1000 women screened in the FFDM group (p<0.001). The recall rate and cancer detection rates (overall, invasive and pure ductal carcinoma in situ) were all significantly higher with FFDM for lesions presenting as microcalcifications. Conclusions: The higher cancer detection rate with FFDM in this study was due to improved detection of microcalcifications. However, this was achieved at the cost of a higher recall rate and a higher B3 rate, indicating that overtreatment may be problematic with digital mammography.